2011
DOI: 10.1152/ajpregu.00272.2011
|View full text |Cite
|
Sign up to set email alerts
|

Distension of the uterus induces HspB1 expression in rat uterine smooth muscle

Abstract: White BG, MacPhee DJ. Distension of the uterus induces HspB1 expression in rat uterine smooth muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Our Pathway Studio results revealed that HSPB1 is significantly associated with reproductive disease (implantation failure). It is reported that HSPB1 protein is overexpressed in uterine distension during pregnancy, as well as inducing the distension of the myometrium, owing to the growing fetus [ 123 , 124 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our Pathway Studio results revealed that HSPB1 is significantly associated with reproductive disease (implantation failure). It is reported that HSPB1 protein is overexpressed in uterine distension during pregnancy, as well as inducing the distension of the myometrium, owing to the growing fetus [ 123 , 124 ].…”
Section: Resultsmentioning
confidence: 99%
“…This model has been previously used to study the effect of uterine distension or stretch on numerous genes and proteins including the gap junction protein GJA1 (Ou et al 1997), the heat shock protein CRYAB (Nicoletti et al 2016) and signaling kinases such as MAPK14 (Oldenhof et al 2002). Virgin female rats were anaesthetized and underwent a unilateral tubal ligation procedure as previously described (White and MacPhee 2011). Animals were monitored post-operatively and allowed to recover for at least 5 days before matings were attempted.…”
Section: Tissue Collectionmentioning
confidence: 99%
“…We previously reported that Hspb1 mRNA expression was significantly increased during late pregnancy in the rat myometrium, that pS15-HSPB1 detection significantly increased during late pregnancy and labour, and that pS15-HSPB1 was induced by uterine distension (White et al. 2005 ; White and MacPhee 2011 ). Furthermore, pS15-HSPB1 had a predominantly membrane-associated localization in situ within cells of the circular and longitudinal muscle layers; however, pS86-HSPB1 was not examined.…”
Section: Introductionmentioning
confidence: 99%
“…This model has been used previously to study the effect of uterine distension or stretch on numerous genes and proteins, including the gap junction protein GJA1, the heat shock protein aBcrystallin (CRYAB) and signalling kinases such as mitogenactivated protein kinase (MAPK) 14 (Ou et al 1997;Oldenhof et al 2002;Nicoletti et al 2016). Virgin female rats were anaesthetised and underwent a unilateral tubal ligation procedure as described previously in detail by White and MacPhee (2011). Animals were monitored postoperatively and allowed to recover for at least 5 days before matings were attempted.…”
Section: Tissue Collectionmentioning
confidence: 99%